Identification of an important immunological difference between virulent varicella-zoster virus and its avirulent vaccine: viral disruption of dendritic cell instruction - Gutzeit, Cindy; Raftery, Martin J.; Peiser, Matthias; Tischer, Karsten B.; Ulrich, Martina; Eberhardt, Melanie; Stockfleth, Eggert; Giese, Thomas; Sauerbrei, Andreas; Morita, Craig T.; Schönrich, Günther (The journal of immunology, 2010)
Virulent varicella-zoster virus (VZV) can spread in immunocompetent humans, resulting in symptoms mostly of the skin. In contrast, vaccine Oka (V-Oka), the attenuated VZV vaccine strain, only rarely causes clinical reactions. The mechanisms underlying these pathogenetic differences are unclear. In this study, we comparatively analyzed the ability of virulent VZV and V-Oka to modulate instruction of dendritic cells (DCs) by innate signals. DCs isolated from normal human skin were susceptible to infection with VZV and V-Oka. Moreover, inflammatory DCs, which play a crucial role in the stimulation of Th1 immune responses, accumulated in herpes zoster lesions. Infection of inflammatory DCs generated in vitro with virulent VZV or V-Oka resulted in upregulation of CD1c. Upon coculture with CD1c-restricted innate cells, DCs developed a mature phenotype whether infected with virulent VZV or V-Oka. Intriguingly, a striking difference was detected on the functional level. The release of IFN-gamma and IL-12, the signature cytokines of Th1 responses, was enhanced by V-Oka but blocked by virulent VZV. V-Oka and virulent VZV efficiently synergized with CD40L, eliminating the possibility that CD40 signaling was a target of VZV-associated immune evasion. Instead, virulent VZV selectively interfered with signaling through TLR2, which is known to sense VZV. Thus, virulent VZV subverts Th1-promoting instruction of human DCs by blocking TLR2-mediated innate signals that prime IL-12 production by DCs. Taken together, our results demonstrate a novel immune-evasion mechanism of virulent VZV that has been lost during the attenuation process leading to the VZV vaccine strain.